2012
DOI: 10.3174/ajnr.a2924
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging of the Normal Pediatric Spinal Cord Using an Inner Field of View Echo-Planar Imaging Sequence

Abstract: BACKGROUND AND PURPOSE: DTI in the brain has been well established, but its application in the spinal cord, especially in pediatrics, poses several challenges. The small cord size has inherent low SNR of the diffusion signal intensity, respiratory and cardiac movements induce artifacts, and EPI sequences used for obtaining diffusion indices cause eddy-current distortions. The purpose of this study was to 1) evaluate the accuracy of cervical spinal cord DTI in children using a newly developed iFOV sequence with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 39 publications
(41 reference statements)
2
52
0
Order By: Relevance
“…5,8 It has also been reported that in adult cervical SC DTI, there is good intra-and interobserver variability. 16 In our current study, we have shown that within the cervical and thoracic SC, DTI values showed moderate-to-strong repeatability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5,8 It has also been reported that in adult cervical SC DTI, there is good intra-and interobserver variability. 16 In our current study, we have shown that within the cervical and thoracic SC, DTI values showed moderate-to-strong repeatability.…”
Section: Discussionmentioning
confidence: 99%
“…The inner FOV sequence was based on a single-shot echo-planar imaging sequence for DWI with 2D-selective radiofrequency excitations, which improve the SNR and reduce geometric distortions in SC imaging, described in detail elsewhere. 5,10 Manual shim volume adjustments were also performed before data acquisition to restrict the adjustment volume to the anatomy of interest as much as possible. Diffusion tensor images were acquired axially by using 2 overlapping slabs, in the same anatomic location prescribed for the T2 gradient-echo images, to cover the cervical (C1-upper thoracic region) and thoracic (upper thoracic-L1) SC (Fig 1).…”
Section: Mr Imaging Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…There are even less studies in children and hardly any normative data [5,6,11,12]. Age-specific normative data are necessary to identify and grade spinal cord pathology in developing children.…”
Section: Methodsmentioning
confidence: 99%